2010
DOI: 10.1136/vr.c4827
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pasteurella multocida and other respiratory pathogens in the nasal tract of Scottish calves

Abstract: The prevalence of Pasteurella multocida, a cause of bovine respiratory disease, was studied in a random sample of beef suckler and dairy farms throughout Scotland, by means of a cross-sectional survey. A total of 637 calves from 68 farms from six geographical regions of Scotland were sampled between February and June 2008. Deep nasal swabs were taken, and samples that were culture-positive for P multocida were confirmed by PCR. Prevalence of P multocida was 17 per cent (105 of 616 calves); 47 per cent of farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
(18 reference statements)
6
28
0
2
Order By: Relevance
“…All methods were used as per the manufacturer's instructions. We have previously demonstrated that the QIAamp Viral RNA kit co-purifies BoHV-1 DNA from low cellularity samples [29] and, as BoHV-1 produces viral RNA during replication in tissues, for simplicity of clinical sample preparation we did not explicitly extract DNA for BoHV-1 detection. Phosphate buffered saline (PBS) was used as an extraction control for all extraction methods.…”
Section: Methodsmentioning
confidence: 99%
“…All methods were used as per the manufacturer's instructions. We have previously demonstrated that the QIAamp Viral RNA kit co-purifies BoHV-1 DNA from low cellularity samples [29] and, as BoHV-1 produces viral RNA during replication in tissues, for simplicity of clinical sample preparation we did not explicitly extract DNA for BoHV-1 detection. Phosphate buffered saline (PBS) was used as an extraction control for all extraction methods.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, a high prevalence of BRSV infection has been observed in Belgium [42]. Circulation of the virus in Scotland has also been reported, although conclusive figures regarding BRSV prevalence are not available [43]. Furthermore, the presence of antibodies in bulk tank milk samples has been reported in herds from England [44].…”
Section: Epidemiology Of Brsvmentioning
confidence: 99%
“…It has been shown to cause respiratory disease in many animals, including cattle [2], sheep [3] and pigs [4,5] although it is also found in the respiratory tract of apparently healthy animals [6]. The organism also causes haemorrhagic septicaemia (HS) in bovids, mainly in South and Southeast Asia and sub-Saharan Africa [7].…”
Section: Introductionmentioning
confidence: 99%